Intrathecal IgM Synthesis Is Associated with Spinal Cord Manifestation and Neuronal Injury in Early MS. Issue 6 (9th April 2022) - Oechtering, Johanna; Lincke, Therese; Schaedelin, Sabine; Décard, Bernhard F.; Maceski, Aleksandra; Orleth, Annette; Meier, Stephanie; Willemse, Eline; Buchmann, Arabella; Khalil, Michael; Derfuss, Tobias; Benkert, Pascal; et al.
Abstract : Objective: Intrathecal Immunoglobulin M synthesis (IgMIntrathecal Fraction (IF) + ) and spinal MRI lesions are both strong independent predictors of higher disease activity and severity in multiple sclerosis (MS). We investigated whether IgMIF + is associated with spinal cord manifestation and higher neuroaxonal damage in early MS. Methods: In 122 patients with a first demyelinating event associations between (1) spinal versus (vs) non‐spinal clinical syndrome (2) spinal vs cerebral T2‐weighted (T2w) and (3) contrast‐enhancing (CE) lesion counts with IgGIF + (vs IgGIF − ) or IgMIF + (vs IgMIF − ) were investigated by logistic regression adjusted for age and sex, respectively. For serum neurofilament light chain (sNfL) analysis patients were categorized for presence or absence of oligoclonal IgG bands (OCGB), IgGIF and IgMIF (>0% vs 0%, respectively): (1) OCGB − /IgGIF − /IgMIF − ; (2) OCGB + /IgGIF − /IgMIF − ; (3) OCGB + /IgGIF + /IgMIF − ; and (4) OCGB + /IgGIF + /IgMIF + . Associations between categories 2 to 4 vs category 1 with sNfL concentrations were analyzed by robust linear regression, adjusted for sex and MRI parameters. Results: Patients with a spinal syndrome had a 8.36‐fold higher odds of IgMIF + (95%CI 3.03–23.03; p < 0.01). Each spinal T2w lesion (odds Ratio 1.39; 1.02–1.90; p = 0.037) and CE lesion (OR 2.73; 1.22–6.09; p = 0.014) was associated with an increased risk of IgMIF + (but not of IgGIF + ); this was not the case for cerebral lesions. OCGB + /IgGIF + /IgMIF + category patients showed highest sNfL levels (estimate:1.80; 0.55–3.06; p < 0.01). Interpretation: Intrathecal IgM synthesis is strongly associated with spinal manifestation and independently more pronounced neuroaxonal injury in early MS, suggesting a distinct clinical phenotype and pathophysiology. ANN NEUROL 2022;91:814–820